Ultra-high temperature ceramics: Materials for extreme environments. (1st March 2017) - Fahrenholtz, William G.; Hilmas, Greg E.
Abstract: This paper identifies gaps in the present state of knowledge and describes emerging research directions for ultra-high temperature ceramics. Borides, carbides, and nitrides of early transition metals such as Zr, Hf, Nb, and Ta have the highest melting points of any known compounds, making them suitable for use in extreme environments. Studies of synthesis, processing, densification, thermal properties, mechanical behavior, and oxidation of ultra-high temperature ceramics have generated a substantial base of knowledge, but left unanswered questions. Emerging research directions include testing/characterization in extreme environments, composites, computational studies, and new materials. Graphical abstract: